2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009419
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary phantom hand and finger movements in transhumerai amputees could be used to naturally control polydigital prostheses

Abstract: An arm amputation is extremely invalidating since many of our daily tasks require bi-manual and precise control of hand movements. Perfect hand prostheses should therefore offer a natural, intuitive and cognitively simple control over their numerous biomimetic active degrees of freedom. While efficient polydigital prostheses are commercially available, their control remains complex to master and offers limited possibilities, especially for high amputation levels. In this pilot study, we demonstrate the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…The present study confirmed our previous results ( [12], [13], [21]) that phantom mobility is classifiable, even before training, with overall classification success rates that are comparable to values found in the literature, using other methods in a clinical setting where amputees trained the PR controller using static muscle contractions, sometimes with additional instructions such as varying EMG amplitudes [31], [35]. If so, is phantom training at home useful?…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study confirmed our previous results ( [12], [13], [21]) that phantom mobility is classifiable, even before training, with overall classification success rates that are comparable to values found in the literature, using other methods in a clinical setting where amputees trained the PR controller using static muscle contractions, sometimes with additional instructions such as varying EMG amplitudes [31], [35]. If so, is phantom training at home useful?…”
Section: Discussionsupporting
confidence: 91%
“…The kinematics of the mimicked phantom finger movements were recorded on the intact hand using a Cyberglove® II, at a frequency of 100 Hz. Details on the calibration of the Cyberglove have been reported previously [12], [22]. Global hand movements around the wrist were recorded with an inertial measurement unit (IMU, nine degree-of-freedom Sensor Stick from Sparkfun ®) that was attached to the dorsal surface of the glove.…”
Section: Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been quite extensively studied for below-elbow amputees whose residual limb usually still contains the muscles that mobilized the fingers before the amputation, and, therefore, provide an adapted measurement site together with relatively strong myoelectric signals. While first attempts of adaptation of these approaches to above-elbow amputees date back to the 70s with pioneering work like (Wirta et al, 1978 ), several studies recently tried to revive such approach using updated classification techniques, specifically of phantom-limb-mobility-related EMG signals (Jarrasse et al, 2017b ; Gaudet et al, 2018 ), even extended to individual finger movement decoding (Jarrasse et al, 2017a ). Also, recent work on the treatment of phantom limb pain with help of virtual reality (e.g., Ortiz-Catalan et al, 2016 ) illustrates the possibility of decoding these PLM-associated EMG patterns measured on the residual limb of transhumeral amputees.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these characteristics are only a related subcategory of the factors that instigate inconsistencies in interpreting the time and occurrence-based statistical features of the sEMG signals. The evaluation of these factors was conducted by researchers who have obtained significant results from their analysis (Jarrasse et al, 2017 ). Techniques for monitoring muscle activity are employed to measure and analyze the performance of machines and equipment, as well as to evaluate the physical condition of their operators (Hyodo et al, 2012 ; Hong et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%